Pengaruh Corporate Governance (CG), Corporate Social Responsibility (CSR), dan Green Accounting Terhadap Financial Performance - Syakila, Ananda; Halmawati, Halmawati (Universitas Negeri Padang, 2025)
This study aims to investigate the impact of Corporate Governance (CG), Corporate Social Responsibility (CSR), and Green Accounting on Financial Performance. This research is categorized as causal research utilizing a quantitative approach. The study was conducted on companies within the basic materials sector listed on the Indonesia Stock Exchange from 2021 to 2023, employing purposive sampling as the sampling method. A total of 67 samples were collected over the three-year research period. The data analysis technique employed was multiple linear regression using SPSS version 29. The findings of this research indicate that Corporate Governance (CG), as measured by the audit committee and independent board of commissioners, does not significantly influence Financial Performance; Corporate Social Responsibility (CSR) also shows no significant effect on Financial Performance. Conversely, Green Accounting, measured by environmental costs, has a significant negative impact on Financial Performance.